Combined prediagnostic lifestyle factors and survival of breast, colorectal and lung cancer in the Norwegian Women and Cancer (NOWAC) study: a prospective cohort study - Tonje Braaten; Kristin Benjaminsen Borch; Jill Tinmouth; Therese Haugdahl Nøst; Sairah Lai Fa Chen; Torkjel Manning Sandanger (BMJ Open)
Background With improvements in cancer treatment and early detection, the number of people living with cancer is increasing.Objective This study aimed to investigate the association between combined prediagnostic lifestyle factors, assessed by a Healthy Lifestyle Index (HLI) score, and mortality among women diagnosed with breast cancer (BC), colorectal cancer (CRC) and lung cancer (LC).Design Prospective cohort.Setting Women residing in Norway, general population.Participants Our analysis included 5032, 2468 and 1594 women from the Norwegian Women and Cancer study diagnosed with BC, CRC and LC, respectively, who responded to a questionnaire between 1996 and 2014.Exposure measures HLI score measured prior to cancer diagnosis. The HLI combines physical activity level, body mass index, smoking behaviour, alcohol consumption and dietary habits.Outcome measures We estimated HRs and 95% CIs using Cox proportional hazard models for all-cause and site-specific cancer mortality.Results After median follow-up times of 9.8, 7.1 and 5.9 years for BC, CRC and LC cases, respectively, there were 912, 902 and 1094 all-cause deaths; and 509 BC deaths, 679 CRC deaths and 961 LC deaths. For women diagnosed with BC, a 1-point HLI score increment was associated with a 6% lower all-cause mortality rate (HR: 0.94, 95% CI: 0.92 to 0.97). The data were compatible with no association for the estimated 3% lower BC mortality rate (HR: 0.97, 95% CI: 0.94 to 1.00) among women diagnosed with BC, and for the estimated 3% lower all-cause (HR: 0.97, 95% CI: 0.95 to 1.00) and 2% lower CRC mortality rates (HR: 0.98, 95% CI: 0.95 to 1.01) among women diagnosed with CRC. For women diagnosed with LC, prediagnostic HLI score was not associated with all-cause (HR: 1.00, 95% CI: 0.98 to 1.02) or LC mortality rates (HR: 1.00, 95% CI: 0.98 to 1.03).Conclusions We observed that a higher HLI score measured before cancer diagnosis was associated with lower all-cause and, possibly, lower BC mortality among Norwegian women diagnosed with BC; and a possible lower all-cause and CRC mortality among those diagnosed with CRC. Smoking was likely responsible for the observed associations.